La Cuevona de Avín (Avín, Asturias, North Spain): A new Late Pleistocene site in the lower valley of the River Güeña - Álvarez-Fernández, Esteban (2022)
The archaeological investigations carried out in the last twenty years in the Lower Valley of the River Gliena (Asturias, central part of northern Spain) have documented different prehistoric sites, particularly with Middle and Upper Palaeolithic occupations. This paper presents the first results of the archaeological excavation carried out in the cave of La Cuevona de Avin. From the systematic study of the biotic and abiotic remains, a total of three occupation phases (Phases 1 to 3) have been determined, dated in the Late Pleistocene. The lithic studies indicate the use of local raw materials (mainly quartzite), but also regional ones (different types of flint) in the whole sequence. Retouched implements are typologically representative only during the Upper Magdalenian (Phase II) and use-wear analysis indicates the manufacture and use of artefacts in situ during this phase. Archaeozoological studies reveal continuity in subsistence strategies throughout the sequence, noting specialization in red deer hunting during the Azilian (Phase I), and more diversified prey in the older phases of the sequence.